Identification of TENORM in Zirconium Oxychloride with Gamma Spectrometry - Kharistya Rozana; Devi Swasti Prabasiwi; Dewi Puspa Ariany (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Abstract: Gamma spectrometer used to determine the type and activity of gamma emitting radionuclides, such as the measurement of TENORM (Th-232, U-238, Ra-26 dan K-40) in the zirconium oxychloride or environmental radioactivity. This research was carried out to know each the TENORM on the zirconium oxychloride (ZrOCl2.8H2O) which accommodation of environment data the radioactivity in draft job safety about the workers. Zirconium oxychloride is a result of chloride acid leaching process from sodium zirconate, containing uranium and thorium, so that it has the potential for contamination and increase the radiation exposure. The instrument used for counting by HPGe detector and the spectrum were analyzed further using software Genie 2000. Mean measured activity concentrations (radioactivity) of U-238, Th-232, Ra-226 and K-40 respectively were 13,43±0,876 Bq/kg, 12,040±1,483 Bq/kg, 11,400±0,582 Bq/kg dan 32,940±3,270 Bq/kg.